Working Memory in Overweight Boys during Physical Education Classes - Aymen Hawani; Anis ben Chikha; Wael Zoghlami; Mohamed Abdelkader Souissi; Omar Trabelsi; Maher Mrayeh; Antonella Muscella (MDPI AG, 2023)
This study examined the effect of small-sided football games (SSFG) and small-sided Ultimate Frisbee games (SSUFG) on working memory, response times, and feeling mood of boys with overweight. Twenty-eight boys (age 12.23 ± 1.58 years) participated in two trials during physical education lessons (20-min SSFG and 20-min SSUFG) in a counterbalanced, randomized crossover design. The response times and feeling mood were measured for all participants post-exercise through the Sternberg paradigm and feeling scale. For the response times, the paired samples t-test revealed a significantly better reaction time after SSUFG at the "One item level" of the Sternberg paradigm (p = 0.014, Hedges' g = 0.27, small effect) and (p = 0.010, Hedges' g = 0.74, medium effect), at "Three item level" (p = 0.000106, Hedges' g = 1.88, very large effect). The SSFG also showed vigor at the "Five item level" (p = 0.047, Hedges' g = 0.61, medium effect). For the feeling mood, the feeling score was significantly higher after the SSUFG session than the SSFG session and the increase in feeling scores observed after switching from SSFG to SSUFG was significantly different (p < 0.001) from the decrease observed in feeling scores after switching from SSUFG to SSFG. Therefore, the results of the study allow the teacher to introduce new sports and reflect on the motor tasks he or she proposes for boys with overweight during physical education classes.